1992
DOI: 10.1111/j.1469-8137.1992.tb01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excess nitrogen and phosphorus starvation on the extramatrical mycelium of ectomycorrhizas of Pinus sylvestris L.

Abstract: SUMMARYThe effect of excess nitrogen alone, and in combination with phosphorus and magnesium starvation, on the production of extramatrical mycelium was studied in Scots pine seedlings ectomycorrhizal with Laccaria bicolor (R. Mre.) Orton, Hebeloma crustuliniforme (Bull, ex St-Amans) Quel. and Suillus bovinus (L. ex Fr.) O. Kuntze. Seedlings were grown in a semi-hydroponic cultivation system and the ergosterol assay was used to estimate fungal biomass. The mycelial biomass increased rapidly when N was kept low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
1
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 22 publications
10
118
1
4
Order By: Relevance
“…Wallander and Nylund (1992) reported that S. bovinus was more sensitive to N additions than was Laccaria bicolor when both were grown on Pinus sylvestris in a semi-hydroponic medium. In a microcosm experiment conducted by Arnebrant (1994), two isolates of P. involutus, one isolate of S. bovinus, and two additional unidentified species of ECM fungi were exposed to increasing N availability.…”
Section: Elevated Comentioning
confidence: 99%
“…Wallander and Nylund (1992) reported that S. bovinus was more sensitive to N additions than was Laccaria bicolor when both were grown on Pinus sylvestris in a semi-hydroponic medium. In a microcosm experiment conducted by Arnebrant (1994), two isolates of P. involutus, one isolate of S. bovinus, and two additional unidentified species of ECM fungi were exposed to increasing N availability.…”
Section: Elevated Comentioning
confidence: 99%
“…In natural forest ecosystems, no data are available for uptake rates of specific root sections or hyphae (George & Marschner, 1996), though laboratory experiments assessing fungal biomass showed that production of extramatrical mycelium decreases with increasing N concentration (Wallander & Nylund, 1992). Since the Ho$ glwald site is exposed to high loads of N, it is unlikely that the rhizomorphs make a considerable contribution to nutrient uptake.…”
Section: mentioning
confidence: 99%
“…Nevertheless, because the extraradical mycelium is the main ECM fungal component in terms of nutrient mobilization and supply to the host plant for several species (Read, 1984 ;Read, Francis & Finlay, 1985 ;Read, 1992 ;Rousseau, Sylvia & Fox, 1994 ;Bending & Read, 1995) more detailed field investigations are required. Laboratory experiments indicate a negative correlation between increasing N availability and development of the extraradical mycelium : Wallander & Nylund (1992) investigated the effect of excess N alone and in combination with P and Mg starvation in a semi-hydroponic cultivation system with Pinus sylvestris seedlings infected with Laccaria bicolor, Hebeloma crustuliniforme and Suillus bovinus. Whereas the mycelial biomass increased rapidly at concentrations of 0n7-1n4 m NH % + the production of extraradical mycelium by all species ceased in the presence of high N concentrations (14n3 m NH % + ).…”
Section:        mentioning
confidence: 99%